2017
DOI: 10.1002/jcb.25889
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Corin in the Progression of Diabetic Erectile Dysfunction in a Rat Model by Down-Regulating ANP /NO/cGMP Signal Pathway

Abstract: This study was aimed to analyze the potential role of Corin in the procession of diabetic ED and to explore the underlying mechanism. Diabetic ED rat model was constructed and the characteristics of diabetic ED and control rats were recorded at 4, 8, 12, and 16 weeks. qRT-PCR and Western bloting were used to detected the mRNA and protein levels. Intracellular cGMP detection was accomplished using a commercial radioimmunoassay method. Vascular endothelial cell from rat corpus cavernosum spiral artery was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…21 We showed that a lack of Corin in HK-2 cells could attenuate endothelial migration of EA.hy926 cells through paracrine crosstalk that is likely mediated by ANP. 12 It is plausible that impaired Corin-ANP signaling in diabetes is a common mechanism leading to endothelial dysfunction and subsequent diabetic microvascular complications. 11 Consistently, Jian Wang et al demonstrated that a lack of Corin could inhibit vascular endothelial cell viability.…”
Section: Xue Et Almentioning
confidence: 99%
See 4 more Smart Citations
“…21 We showed that a lack of Corin in HK-2 cells could attenuate endothelial migration of EA.hy926 cells through paracrine crosstalk that is likely mediated by ANP. 12 It is plausible that impaired Corin-ANP signaling in diabetes is a common mechanism leading to endothelial dysfunction and subsequent diabetic microvascular complications. 11 Consistently, Jian Wang et al demonstrated that a lack of Corin could inhibit vascular endothelial cell viability.…”
Section: Xue Et Almentioning
confidence: 99%
“…11 Consistently, Jian Wang et al demonstrated that a lack of Corin could inhibit vascular endothelial cell viability. 12 It is plausible that impaired Corin-ANP signaling in diabetes is a common mechanism leading to endothelial dysfunction and subsequent diabetic microvascular complications.…”
Section: Xue Et Almentioning
confidence: 99%
See 3 more Smart Citations